The Study Strength of Laminated Bamboo Pedestal Using Bolted Joints - Andi Yusra; Zakia Zakia; Sri Kurniati; Dewi Purnama Sari (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Bamboo has properties that vary from the joint. This study aims to investigate the effect of diameter change on the strength test of laminated bamboo cones, the degree of damage that occurs in laminated bamboo specimens, and the connection tool. The purpose of this study is to investigate the effect of diameter change on the strength test of laminated bamboo cones, to investigate the degree of damage that occurs in laminated bamboo specimens, and to determine the static load that can be withstood. Deformation characteristics under working load according to [1]. The method used is the half-hole method. In this study, we found that changes in bolt diameter affected the average pivot strength (Fe), with stress increasing with increasing bolt diameter. This study was conducted to determine the properties of the static load that can be endured and the deformation that occurs in laminated bamboo under load. To get the data, we need to do laboratory tests. Bamboo pivot strength test to find Fe max and Fe 5%. A long tube with a width of 39.5 cm, a height of 45 cm, and a length of 450 cm. During the pivot strength test, the broken sample had a zigzag change of 10 mm in diameter. As a result of the strength test of laminated bamboo sticks, the average maximum Fe values of screws with diameters of 8 mm and 10 mm were 85584 MPa and 91930 MPa, respectively. The average (Fe 5%) values for 8 mm and 10 mm diameter screws are 74.819 MPa and 65.594 MPa.